Evaluating the socio-economic factors impacting on the dietary diversity of elderly people in Sharpeville - Mwadiwa, Rufaro Janet (Vaal University of Technology, 2022)
Rationale and objectives: Underlying and motivating the study was the need to evaluate the socio-economic factors impacting on the dietary diversity of the elderly people attending the Sharpeville Day Care Centre for the Aged (SDCCA). The assessment was based on the initial baseline surveys of 2004 and 2009 and all the converging results of the mutually related research data conducted at the centre to 2016. Methodology: A quantitative longitudinal population-based design was used for this study. In total, the sample size was n=302 respondents with 99 screened for 2004, 99 screened for 2009 and 104 respondents for this study. A variety of socio-economic variables (old age pension grant, household income, household contributions and education attainment) were used to measure the objectives. Different types of questionnaires were used as measuring instruments for all the variables of the study. These included socio- demographic questionnaires, administered to determine the socio-economic characteristics of the elderly and the 24-hour recall questionnaire, to identify actual food intake measured against the estimated average requirements (EARs) and food frequency questionnaires to determine the respondent’s food variety score over a period of one week. The completed questionnaires were captured on a Microsoft Excel spreadsheet by the researcher. The analysis and correlation of the data were done using the Statistical Package for the Social Sciences (SPSS), version 25.0, with the assistance of a statistician. Results: From the baseline interventions, the dietary intake results revealed a poor dietary intake; thus, contributing to inadequate estimated average requirements (EARs) and adequate intakes (AIs) of nutrients. In this study, a carbohydrate-based diet was mainly consumed with insignificant intake of dairy and legumes despite a medium dietary diversity score. The energy intake for both the women (4 920.77kJ), which was equivalent to 48.75 percent of the EARs and males (4 945.61kJ), equivalent to 38.39 percent of the EARs, did not meet the recommended EER energy intake, with no significant variance amongst women and men (p=0.923). Both the FFQ and 24-hour recall indicated that carbohydrate and starch form the basis of most meals consumed. repeat. Longitudinally, the socio-economic variables had a statistically exchangeable impact on the dietary diversity scores, indicating either no relationship (0), negative (r=-1) or positive (r=1) associations between the food groups. Hypothetically, the hypothesis supported the results, showing that food consumption and dietary diversity had positive and negative significance these are two hypotheses (one positive and the other negative) to socio-economic variables within the elderly community is it not the other way around. Socio-economic variable having impact on food consumption and dietary diversity? Conclusion: All the respondents that took part in the study were unemployed pensioners and were the only contributors in the households, thus, clarifying the low total earnings in the elderly households. Furthermore, the majority of the respondents cared for more than one family member in the household. As a result, less money was available to spend on food diversity to maintain a healthy lifestyle. The low levels of education attainment contributed to poor nutrition knowledge. Hence, in order to promote longevity and healthy ageing, there is need for an integrated (traditional- modern food processes) nutritional education by public health services on food-based dietary diversity rather than only nutrient-based dietary. These results support the hypotheses that the elderly of SDCCA are constrained to making better food choices due to low incomes, low pension pay-outs, low educational levels and low household contributions.
D. Tech. (Department of Tourism and Integrated Communication, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Elderly; Socio-economic factors; Dietary diversity; Longitudinal study; Malnutrition; Energy intake; Dissertations, Academic -- South Africa.; Older people -- Nutrition -- South Africa -- Evaluation.